Bank Efficiency in Selected Developing Countries - Chan, Sok Gee (2008)
The efficiency of the banking system is essential especially in the developing countries because the banking system serves as the nerve for overall financial development in terms of economic growth at the macro level (Andersen and Trap,2003; Khan and Senhadji, 2000; Levine, 2002). This is because an efficient banking system will help to boost national income and wealth. Consequently, it would be able to encourage depositors to make more deposits and as a result encourages monetary advancement.This study aimed to investigate the existence of cost efficiency and profit efficiency among the banking sector in selected developing countries in the Asia, Middle East, and the African region from 2000 to 2005. A comparison between the cost and profit efficiency from the selected developing countries in the three regions was done in this study. In addition, this study also aims to identify the determinant of the bank efficiency level from both micro-level and macro-level perspectives.The parametric approach and non-parametric approach were employed in this study. From the estimation results from parametric approach, commercial banks in the selected developing countries are cost efficient. This result is consistent with most of the literatures. Next, the estimation results of the cost and profit efficiency indicate that commercial banks in the Middle Eastern and North African region are the most cost efficient followed by commercial banks in the Asian region. The DEA results reported a relatively low cost efficiency scores as compared to the stochastic frontier models. A further decomposition of cost efficiency into technical and allocative efficiency indicates that the commercial banks’ cost inefficiency are actually due to technical inefficiency.It is also found that the bank-specific factors did influence the efficiency level of the commercial banks in the three regions under analysis. The efficiency scores of the commercial banks in terms of cost and profit efficiency across regions are found to have negative relationship with the equity to total assets ratio. On the other hand, the return on assets is found to be positively related to profit efficiency of the commercial banks over the regions. The positive relationship between loans to total assets ratios and profit efficiency indicates specialization in lending activities enable commercial banks to be more efficient. Cost efficiency of the commercial banks in the Asian region is found to positively related to real GDP per capita, banking institutions’ credit to the private sector, and market concentration and negatively related to trade openness. On the other hand, broad money to GDP ratio is positively related to profit efficiency of the commercial banks in the Asian region. However, credit extended to the private sector seems to be negatively related with profit efficiency level of the commercial banks in the region. This might be due to the reasons that most of the credit extended to the private sectors were channelled to the priority sectors and Small and Medium Industries with a lower rate of interest charged. Bank efficiency in the Middle Eastern and North African regions seems to be more prone towards the factors of openness such as trade openness and financial development. Whereas the main macroeconomics variables are found to exert strong influences over the bank efficiency in commercial banks in the African region.